Formulation and Physical Quality Testing of Solid Soap From a Combination of Citronella Oil with Patchouli Leaf Oil Againts Staphylococcus aureus Bacteria - Pradana, Anugrah Riska; Hamzah, Hasyrul; Dewi, Sinta Ratna; Wirnawati, Wirnawati (Journal of Islamic Pharmacy, 2024)
Bacteria on the skin can cause infections ranging from mild to quite serious. Bacteria that are commonly found on human skin are the pathogenic bacteria Staphylococcus aureus. The choice for making antibacterial solid soap based on active ingredients from patchouli oil and citronella oil is that this oil has inhibitory power in the growth of bacteria on the skin, one of which is Staphylococcus aureus. The aim of this research is to determine how large the inhibition zone is produced by the antibacterial solid soap formulation and to determine the characteristics and physical quality tests of the solid soap preparation combining citronella oil with patchouli leaf oil so that it is safe to use. The method used is a pure experimental method. Data collection was carried out for 4 weeks according to the testing time and then analyzed using the Graphad application. The results of the research on the inhibition zone test used 2 concentrations, namely 50% and 100%, each formulation had different average results, namely at F2 50% the average was 21 mm with a very strong category, at F2 100% the average was 19.5 mm with the strong category, at F3 50% we get an average of 16 mm in the strong category and at F3 100% we get an average of 18.6 mm in the strong category. In the tests that have been carried out, it was concluded that citronella oil and patchouli leaf oil can be made into antiseptic solid soap and can inhibit the growth of Staphylococcus aureus bacteria. The results of testing physical quality characteristics for 4 weeks have met the standard requirements for solid soap.